2021
DOI: 10.21203/rs.3.rs-1073214/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pre-clinical validation of a novel pan-cancer CAR-T cell immunotherapy against nfP2X7

Abstract: Chimeric antigen receptor (CAR)-T immunotherapy is a novel treatment that genetically modifies the patient’s own T cells to target and kill malignant cells. CAR-T cells demonstrated robust clinical activity against certain B-cell malignancies. However, identification of tumour-specific antigens expressed on multiple cancer types, especially on solid cancers, remains a major challenge. P2X purinoceptor 7 (P2X7) is an ATP gated cation channel that forms homotrimers and heterotrimers at the cell surface. When fun… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 45 publications
(75 reference statements)
0
20
0
Order By: Relevance
“…The nfP2X7 peptide-binding domain 16,19,22 was cloned into a well characterised second-generation CAR lentiviral backbone encoding a IgG4 hinge/linker and intracellular domains from 41BB and CD3 zeta, connected by a T2A self-cleaving peptide to a truncated EGFR (EGFRt) reporter as described previously 20 (Supplementary figure 1). Previous work confirmed that the nfP2X7-CAR-T cells act specifically via the P2X7 receptor gene locus and possess on-target specificity and limited off target cytotoxicity.…”
Section: Results Nfp2x7-car-t Cells Are Cytotoxic Against Ovarian Can...mentioning
confidence: 99%
See 4 more Smart Citations
“…The nfP2X7 peptide-binding domain 16,19,22 was cloned into a well characterised second-generation CAR lentiviral backbone encoding a IgG4 hinge/linker and intracellular domains from 41BB and CD3 zeta, connected by a T2A self-cleaving peptide to a truncated EGFR (EGFRt) reporter as described previously 20 (Supplementary figure 1). Previous work confirmed that the nfP2X7-CAR-T cells act specifically via the P2X7 receptor gene locus and possess on-target specificity and limited off target cytotoxicity.…”
Section: Results Nfp2x7-car-t Cells Are Cytotoxic Against Ovarian Can...mentioning
confidence: 99%
“…Previous work confirmed that the nfP2X7-CAR-T cells act specifically via the P2X7 receptor gene locus and possess on-target specificity and limited off target cytotoxicity. 20 Deletion of the P2X7R gene in prostate cancer cell line (PC3), significantly reduced the CAR-T cell-mediated cytotoxicity, when compared with the wild-type PC3 cells. 20 Significant cytotoxicity was observed against cell lines that express nfP2X7 receptor but little cytotoxicity against cell lines that express P2X7 receptor only, or no expression of both nfP2X7 and P2X7 receptor.…”
Section: Results Nfp2x7-car-t Cells Are Cytotoxic Against Ovarian Can...mentioning
confidence: 99%
See 3 more Smart Citations